The IDB in the Caribbean : a partnership for development (IDB WashingtonUS, 2008)
Highlights the IDB's efforts to assist in the economic and social development of seven Caribbean countries viz. The Bahamas, Barbados, Guyana, Haiti, Jamaica, Suriname and Trinidad and Tobago.
Keywords: IDB